Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Konsumen Pada Mini Market Joysmart Sleman - Saputra, Muhammad Fitriyanto (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
The sales level of a product can indicate consumer purchasing decisions. Based on data from Joysmart Sleman mini requests and employee interviews, sales of Joysmart Sleman mini requests have decreased in recent years. This research aims to determine the influence of promotions and prices on purchasing decisions. The type of research used is explanatory research using questionnaire data collection techniques. The method used in This research is quantitative. The population used in this research is consumers who shop and the large sample in this research is 100 consumers of the Joysmart Sleman Minimarket using the Axidental slice method. The methods used in this research include validity tests, reliability tests, normality tests, multiple regression analysis techniques, and analysis of the coefficient of determination, t-test, and F test. The research results show that Promotion influences consumer purchasing decisions, Price influences purchasing decisions, and Promotion and price simultaneously influence consumer purchasing decisions. Related sellers can use the results of this research as material for consideration to increase sales by improving consumer purchasing decisions.